E-democracy -- safeguarding democracy and human rights in the digital age : 8th International Conference, e-Democracy 2019, Athens, Greece, December 12-13, 2019, Proceedings /: 8th International Conference, e-Democracy 2019, Athens, Greece, December 12-13, 2019, Proceedings. (2020) - Unknown
No abstract available